Efektivitas Penggunaan Media Interaktif Berbasis Game Edukatif dalam Meningkatkan Hasil Belajar IPA Siswa SD - Hestiwi Trisna Linayanti; Arif Widyatmoko; Langlang Handayani (Universitas Sebelas Maret, 2025)
This research aims to examine the effectiveness of using interactive media based on educational games in enhancing learning outcomes in science subjects at the elementary school level. By using qualitative literature review methods, various previous studies are analyzed to assess the extent to which game-based learning media can provide a positive impact on the teaching and learning process. The results of the study indicate that educational media based on games not only makes learning more interesting and enjoyable but also significantly can enhance students' motivation to learn, engagement, and achievement of learning outcomes. The use of educational game media proves to be effective and easy to implement, as well as helping students to understand science concepts through more interactive and visual learning experiences. Thus, the use of interactive media based on games is highly recommended as an innovative alternative in creating meaningful and student-centered learning.